2021
DOI: 10.3389/fnut.2021.675640
|View full text |Cite
|
Sign up to set email alerts
|

Methyl-Donor Micronutrient for Gestating Sows: Effects on Gut Microbiota and Metabolome in Offspring Piglets

Abstract: This study aimed to investigate the effects of maternal methyl-donor micronutrient supplementation during gestation on gut microbiota and the fecal metabolic profile in offspring piglets. Forty-three Duroc × Erhualian gilts were assigned to two dietary groups during gestation: control diet (CON) and CON diet supplemented with MET (folic acid, methionine, choline, vitamin B6, and vitamin B12). The body weights of offspring piglets were recorded at birth and weaning. Besides this, fresh fecal samples of offsprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…SCFAs are essential metabolites produced by intestinal microbiota, among which acetic acid, propionic acid and butyric acid account for 90% of SCFAs produced by intestinal microbiota [44]. In the detection of intestinal flora, we found that adding NBAs increased the relative abundance of Lactobacillus and Dialister, and both Lactobacillus and Dialister could increase the content of SCFAs [45,46]. Lactobacillus can use carbohydrates in the gut to produce lactic acid.…”
Section: Discussionmentioning
confidence: 82%
“…SCFAs are essential metabolites produced by intestinal microbiota, among which acetic acid, propionic acid and butyric acid account for 90% of SCFAs produced by intestinal microbiota [44]. In the detection of intestinal flora, we found that adding NBAs increased the relative abundance of Lactobacillus and Dialister, and both Lactobacillus and Dialister could increase the content of SCFAs [45,46]. Lactobacillus can use carbohydrates in the gut to produce lactic acid.…”
Section: Discussionmentioning
confidence: 82%
“…12 Accumulating evidence also suggests that maternal FV consumption increases SAM levels in both mothers and offspring. 15,39 SAM, a metabolite of Met, disrupts the SAMTOR-GATOR1 complex, thereby activating mTORC1 signaling. 40 Therefore, we speculate that FV supplementation may promote SAM production through remethylation pathways, consequently activating the mTORC1 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research has demonstrated that Met protects cells and supports organ development in combating oxidative stress by elevating SAM levels 12 . Accumulating evidence also suggests that maternal FV consumption increases SAM levels in both mothers and offspring 15,39 . SAM, a metabolite of Met, disrupts the SAMTOR‐GATOR1 complex, thereby activating mTORC1 signaling 40 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations